Be frank with me - Johnson, Julia Claiborne (William Morrow, an imprint of HarperCollins Publishers, 2016)
Reclusive literary legend M. M. 'Mimi' Banning has been holed up in her Bel Air mansion for years. But after falling prey to a Bernie Madoff-style ponzi scheme, she's flat broke. Now Mimi must write a new book for the first time in decades, and to ensure the timely delivery of her manuscript, her New York publisher sends an assistant to monitor her progress. The prickly Mimi reluctantly complies, with a few stipulations: No Ivy-Leaguers or English majors. Must drive, cook, tidy. Computer whiz. Good with kids. Quiet, discreet, sane. When Alice Whitley arrives at the Banning mansion, she's put to work right away-as a full-time companion to Frank, the writer's eccentric nine-year-old, a boy with the wit of Noel Coward, the wardrobe of a 1930s movie star, and very little in common with his fellow fourth-graders.